2022
DOI: 10.1093/conphys/coac047
|View full text |Cite
|
Sign up to set email alerts
|

Swimming performance of a pelagic species in the Yangtze River under different exposure modes of the total dissolved gas supersaturation

Abstract: During flood discharges of upstream dams in the Yangtze River, the pelagic fish have a stress risk from total dissolved gas (TDG) supersaturation in the river water. This study took the silver carp as the object and systematically evaluated the effects of TDG supersaturation levels and exposure time on their critical swimming speed (Ucrit) at different temperatures. The external symptoms of gas bubble disease were found when TDG levels exceeded 130%. Both exposure time and TDG level did not significantly impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Previous studies found that fish behavior may be influenced by flow velocities and TDG levels ( Ji et al , 2022 ; Shi et al , 2022 ). In this study, fish were observed to swim randomly under static settings while they were found swimming in the same direction under lotic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that fish behavior may be influenced by flow velocities and TDG levels ( Ji et al , 2022 ; Shi et al , 2022 ). In this study, fish were observed to swim randomly under static settings while they were found swimming in the same direction under lotic settings.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological mechanisms associated with swimming vary with the temperature, and swimming performance differs in response to temperature (Beamish, 1978). Silver carp ( Hypophthalmichthys molitrix ) distributed widely in China was found to exhibit significantly lower swimming ability at the lower temperature within an optimum range (Ji et al, 2022). It can be inferred that the specific ecological characteristics of low temperature and hypoxia in the Qinghai‐Tibet Plateau may greatly limit the swimming performance of these fish species.…”
Section: Discussionmentioning
confidence: 99%
“…A succession of high dams exceeding 200 m have been constructed in the upper reaches of the Yangtze River in China. The effects of TDG supersaturation caused by the operation of these dams on downstream fish have become increasingly noticeable [38][39][40]. Most research into in situ TDG effects has been conducted on salmonids, and research into non-salmonid species is slight in comparison [6].…”
Section: Future Studymentioning
confidence: 99%